Analyze the implementation of Risk Management and Emergency Response in the Workplace: Literatur Review - Ramadhani, Dwi Ajeng; Maulana, Alfian; Naufal, Ahmad Fitra; Hasibuan, Abdurrozzaq (Universitas Ibn Khaldun, 2025)
Based on the analysis of the eight journals, it is concluded that the implementation of risk management and emergency response in the workplace is crucial for building a safe and efficient work environment. Every organization must have a clear and comprehensive plan to handle risks and respond to emergency situations. In addition, training and awareness regarding safety among employees are also important elements in improving preparedness and response to emergencies. This study offers valuable insights for organizations to develop more effective risk management practices and enhance workplace safety and health. This study utilizes library research or literature review. For gathering data for literacy studies, one can reference local and international books, research journals, scientific articles, and studies done by other researchers, the result is based on the analysis of the journals, it is concluded that the implementation of risk management and emergency response in the workplace is crucial for building a safe and efficient work environment. Every organization must have a clear and comprehensive plan to handle risks and respond to emergency situations.